Determinants of Poverty Rate In East Java Province In 2018-2020 - Rahma Ika Fitriana; Maulidyah Indira Hasmarini (Publikasi Indonesia, 2022)
This study aims to determine the magnitude of the determinant effect of the poverty rate in East Java in 2018-2020. This research is a study that uses secondary data obtained from the Central Statistics Agency (BPS) published results. The data used includes Gross Regional Domestic Product (GRDP), Open Unemployment Rate (TPT), population, and per capita income. The method of data collection carried out is the study of documents. The document study itself has various kinds of documents, one of which is a secondary document. Where in this document is taken from the results of other people's reports that have been published. And it will be processed using computer views 10 analysis. The analysis method used is regression analysis with the Panel Least Square (PLS) method which combines time series and cross-section data.